Answer:
The original fraction is
.
Explanation:
Solution,
Let the fraction be'
'.
Where 'x' is the numerator and 'y' is the denominator.
Now according to question, if 2 is added to both the numerator and denominator the value of the fraction becomes 1/2.
So, framing the above sentence in equation form, we get;
![(x+2)/(y+2)=(1)/(2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/7xm57h0ym0szlh03hotbr5hrccgycnhmtu.png)
On using cross multiplication method, we get;
![2(x+2)=y+2\\\\2x+4=y+2\\\\2x+4-2=y\\\\\therefore\ y=2x+2\ \ \ \ equation\ 1](https://img.qammunity.org/2020/formulas/mathematics/high-school/2fwtv830v3ogcjxsfs8ol3yxc9nnt53b0u.png)
Now according to question, if 2 is Subtracted to both the numerator and denominator the value of the fraction becomes 1/3.
So, framing the above sentence in equation form, we get;
![(x-2)/(y-2)=(1)/(3)](https://img.qammunity.org/2020/formulas/mathematics/high-school/4rfcgwh1im4xn3c9jf2c3uhh9wsnw41ijx.png)
On using cross multiplication method, we get;
![3(x-2)=y-2\\\\3x-6=y-2\\\\3x-y=-2+6\\\\3x-y=4 \ \ \ \ equation\ 2](https://img.qammunity.org/2020/formulas/mathematics/high-school/2f2y9adj75n5fbzof3wefflhb7y4r5cves.png)
Now Substituting the equation 1 in equation 1 we get;
![3x-y=4\\\\3x-(2x+2)=4\\\\3x-2x-2=4\\\\3x-2x=4+2\\\\x=6](https://img.qammunity.org/2020/formulas/mathematics/high-school/esxdj59ntna00pvzyjstbq9dtfnuc2g2hf.png)
Now Substituting the value of x in equation 1 we get;
![y=2x+2\\\\y=2*6+2 = 14](https://img.qammunity.org/2020/formulas/mathematics/high-school/lsesvxvk5qsmu43whf5hdsu9lezqr3kkh2.png)
Hence The original fraction is
.